2021
DOI: 10.1073/pnas.2023236118
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal shear stress response in human endothelial cells to atheroprone and atheroprotective conditions

Abstract: The two main blood flow patterns, namely, pulsatile shear (PS) prevalent in straight segments of arteries and oscillatory shear (OS) observed at branch points, are associated with atheroprotective (healthy) and atheroprone (unhealthy) vascular phenotypes, respectively. The effects of blood flow-induced shear stress on endothelial cells (ECs) and vascular health have generally been studied using human umbilical vein endothelial cells (HUVECs). While there are a few studies comparing the differential roles of PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 56 publications
5
28
0
Order By: Relevance
“…This is consistent with other studies that analyzed freshly isolated aortic EC. 34 , 35 Most of our top significant changes in EC gene expression under flow are shared with published data, 18 22 suggesting that EC flow responses are similar when flow parameters are similar, and that species differences or use of primary EC from a particular source (ie, arterial versus venous) in culture do not affect the outcomes. Gene ontology analysis of transcriptome expression heterogeneity changes with flow revealed that protein translation and oxidative metabolism pathways are associated with elevated variance while protein processing is associated with reduced variance, and cell-cell interactions are found in both categories, suggesting complexity in these categories in response to flow.…”
Section: Discussionsupporting
confidence: 72%
“…This is consistent with other studies that analyzed freshly isolated aortic EC. 34 , 35 Most of our top significant changes in EC gene expression under flow are shared with published data, 18 22 suggesting that EC flow responses are similar when flow parameters are similar, and that species differences or use of primary EC from a particular source (ie, arterial versus venous) in culture do not affect the outcomes. Gene ontology analysis of transcriptome expression heterogeneity changes with flow revealed that protein translation and oxidative metabolism pathways are associated with elevated variance while protein processing is associated with reduced variance, and cell-cell interactions are found in both categories, suggesting complexity in these categories in response to flow.…”
Section: Discussionsupporting
confidence: 72%
“…Many of these preclinical findings hold promise for the development of atherosclerosis treatments through pharmacological modulation of the endothelium (e.g., mitigating atherogenic responses or promoting atheroprotective functions in ECs). However, further investigation is required in vitro to determine the generalizability of endothelial responses between vascular cell models (e.g., shared and distinct behaviors of different EC lines under varying flow conditions) ( Maurya et al, 2021 ), as well as in vivo to identify translatability in preclinical models and long-term safety and efficacy in individuals with CVD.…”
Section: Endothelial Cells Govern Site-specificity Of Atherogenesismentioning
confidence: 99%
“…Critically, in vitro culture of ECs still remains problematic. The distinct expressional changes between human EC types in response to different shear stress patterns emphasizes the importance of choosing the right models, with consideration for cell type and contextual interactions, to study endothelialspecific responses in vitro (32). Whilst many research groups have attempted to mimic physiological flow conditions using expensive and/or specialist equipment, the problem still remains that the complex physiological EC environment cannot be mimicked ex vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Perturbations in shear stress can disturb EC mechanosensitive protein signaling, contributing to the pathophysiological angiogenesis in tumor vasculature where low shear stress is experienced, and driving inflammation in atherosclerosis-prone vascular niches and flow-obstructing pathologies where shear stress is disturbed (30,31). Deep sequencing of the transcriptome of human umbilical vein EC (HUVEC) and human aortic EC (HAEC) in response to patterns of shear stress has identified changes in expression of galectins not only in response to specific flow patterns, but also across EC type (32). Collectively, these findings suggest that expression of individual galectins is highly dependent on the tissue microenvironment and that a more in-depth comparison of the patterns of galectin expression across different vascular beds could be insightful for understanding galectin regulation and function in this context.…”
Section: Regulation Of Galectin Expression In Inflammationmentioning
confidence: 99%